New trends in AA amyloidosis with renal involvement: a single-center experience - Nídia Marques; Catarina Oliveira-Silva; Ana Pinho; Ana Teresa Nunes; Susana Sampaio; Ana Oliveira; Isabel Tavares (Brazilian Journal of Nephrology)
Abstract Introduction: In the northwest of Portugal, AA amyloidosis was reported as the most frequent amyloid nephropathy, but it is unclear if the disease’s incidence and outcomes have changed. The authors studied the changing epidemiology, aetiologies, and outcomes of patients with renal AA amyloidosis over the last 40 years. Methods: This is a retrospective single-center cohort study involving patients with renal biopsy-proven AA amyloidosis diagnosed in the northwest of Portugal between 1978 and 2019. The patients were grouped into 14-year cohorts based on the year of diagnosis (CA 1978–1991; CB 1992–2005; CC 2006–2019), and clinical course and outcomes were analyzed. Results: Sixty-nine AA amyloidosis patients were included. The incidence of the disease remained stable in CA (64%) and CB (62.7%) as opposed to the significant decrease in the most recent cohort (44%, p = 0.027). The mean age at presentation increased by ten years from CA to CC. Overall, infections were the leading cause of death, with a significant rise over time (9.1% in CA to 76.9% at CC, p = 0.002). There were no significant global and renal survival differences between the three cohorts. However, the CC patients died at an older age (61.4 years) than the CA (52.3 years). Conclusion: The incidence of AA amyloidosis has been declining over the last 40 years. In contrast, the age at presentation of amyloid nephropathy has been increasing. Global and renal outcomes did not improve, but the average life expectancy increased, suggesting progress in general management and supportive care of renal and underlying pathology.